Методичні засади вибору стратегій випереджаючого інноваційного розвитку промислового підприємства - Ілляшенко, Наталія Сергіївна (Херсонський державний університ, 2019)
Стаття присвячена розробленню методичних засад обґрунтування вибору раціональних стратегій випереджаючого інноваційного розвитку промислового підприємства. В роботі запропонована укрупнена схема вибору стратегій інноваційного розвитку промислових підприємств; систематизовано фактори, які впливають на вибір стратегій інноваційного розвитку підприємства; розроблено рекомендації щодо можливих варіантів реалізації захисної, помірковано-наступальної та випереджаючої інноваційних стратегій на етапах інноваційного і/та життєвого циклу продукції. Отримані результати дозволяють формалізувати вибір варіанту стратегії інноваційного розвитку залежно від стану складових потенціалу підприємства, а також ступеня радикалізації інноваційної діяльності.

The purpose of the article is to develop a methodological basis for selecting rational strategies of advanced innovative development regarding the potential of the enterprise, as well as factors of the external micro-and macro environment. The results of the article complement and deepen the theory of innovative management in terms of forming an approach to modeling the process of selecting innovative development strategies in the concept of innovative advancement. The author, in particular, developed and scientifically substantiated the conceptual approach to the step-by-step selection of the innovative development strategy of the enterprise; updated, supplemented and systematized factors influencing the selection of innovative development strategies of the enterprise; revealed peculiarities of implementation of each type of innovative development strategies of the enterprise – protective, moderately offensive and advanced; highlighted possible options of each type of strategies; developed recommendations for selecting possible ways of application of protective, moderately offensive and advanced strategies of innovative development of the enterprise at the stages of innovative or life cycle of products. Practical implications were carried out at industrial enterprises of the Sumy city (Ukraine) for the formation of a system of selection management by formalized procedures of rational strategies of their innovative development. Its results confirmed practical effectiveness of the obtained scientific and applied results. Developed approaches reflected in decision charts are of scientific novelty. They formalize the choice of a particular strategy depending on the state of components of the industrial enterprise’s potential, as well as the degree of radicalization of innovative activities (product’s innovative or life cycle stages on which the strategy is implemented).
Methodological basis for selection of advanced innovative development strategies for industrial enterprises
Keywords: життєвий цикл; інноваційний бізнес; типи інноваційного випередження; види стратегій; outstripping innovative development; industrial enterprise; types of innovative development strategies; management of the choice of development strategies